PENGARUH KETIDAKPUASAAN KONSUMEN DAN PENCARIAN VARIASI TERHADAP MINAT BERPINDAH MEREK - Brilian, Klaudea; Rohman, Fatchur (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Internet service users show a very rapid increase ranging from 30% to 40% in 2018 to 2021, which was previously only centered on offices, now it is used more in residential areas. Indihome has the highest Top Brand Index in Indonesia, but every year the percentage owned by Indihome has decreased, which means many consumers feel dissatisfied. The objective of this research is to identify the effects of consumer dissatisfaction and variation seeking behavior on the brand switching intention of Indiehome users, the internet service brand of PT. Telkom Indonesia Tbk., in Tulungagung. This study is categorized as explanatory research since it explains the causal relationship between variables through hypothesis testing. The data of this descriptive quantitative research was harvested from Likert-scaled questionnaires distributed to 100 users of Indiehome in Tulungagung, this research finds that consumer dissatisfaction and variation-seeking behavior are positive, which means that higher consumer dissatisfaction and variation-seeking behavior can lead to higher brand switching intention.